Production of five winter forage grasses in pure stands and combined with birds foot trefoil - Schreiner, Henrique Geraldo (Pesquisa Agropecuaria Brasileira, 2014)
Seasonal and yearly production of five forage grasses, in pure stands and combined with birdsfoot trefoil (Lotus corniculatus L.) were studied in the Research Unit of Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) in Colombo, State of Paraná, Brazil the grasses were annual ryegrass (Lolium multiflorum Lam.), common velvet grass (Holcus tlaratus L), tail fescue (Festuca arundinacea Schreb.), bulb canarygrass (Phalaris tuberosa L.) and redtop (Agrostis alba L.). The study started in May of 1971 and was run for two years, in plots fertilized according to sol analysis. Cuts were made at stubble heights of 3cm and 8 cm, every time the vegetation reached the proper grazing height. With a stubble height of 3 cm, in the critical cold period (May 20th to September 20th) annual ryegrass and common velvetgrass revealed the best potential of utilization among all grasses studied, being the same in pure as in combined stands. The average dry matter production, for the two grasses in pure stands were 1,503 and 1,444 kg/ha respectively, and in addition with birds foot trefoil 1,030 and 1,328 kg/ha. Annual yields of common velvetgrass (2,109 kg/ha) and ryegrass (1,952 kg/ha), in pure stands, were higher than other grasses. Annual yields of associations did not show any significant differences. Yields obtained with 8 cm stubble height were much lower tlian at 3 cm but differential effects were similar.